The study on employee participation and involvement (EPI) in Dutch subsidiary in Malaysia - Balakrishnan Parasuraman; Noraani Mustapha; Leonie Kooiker; R.Goodijk; E.M. Kneppers-Heijnert (2013)
Employee participation and involvement (EIP) is an important element for the success of business performance in the organizations (Marchington & Suter 2013 : Parasuraman and Satrya 2011). Employee participation (EP) is a much studied in the Western world. From the literature it is known that EP car have positive effects in the company, as it could increase employee commitment and productivity. The system of labor relations in Netherlands differs a lot from the Malaysian situation. As not much research has been done on EP in Malaysia, and especially not in multinationalcompanies (MNCs), this study has the aim to contribute to contribute to the existing literature, and is an exploratory study focusing on one case study in a Dutch subsidiary, Dutch Lady Malaysia. The main reseach question in this study was: "Which forms of employee participation are developing successfully in a Dutch subsidiary in Malaysia?" The results are retrieved from a qualitative research based on a case study in one Dutch subsidiary. The findings reveal that indirect as well as direct forms of EP are present in the Dutch subsidiary. However, employees can only participate in the company to a limited extent. Factors that stimulate the developmet of EP are the positive management attitudes towards EP, and the supporting core values in the company. Restricting factors have to do with the Malaysian context, as the legislation is not supporting indirect forms of EP (trade unions, and representative bodies), and the Malaysian culture has an important influence in the sense that Malaysian employees often do not dare to speak up. While the positive outcomes of EP are recognized, employees hardly have an influence at the organizational level. Implications of this study are discussed. The findings indicate that there is a need for futher elaborated research in this field.